2022
DOI: 10.21203/rs.3.rs-1404610/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing food’s resource and climate footprints via food waste upcycling

Abstract: The global food system is a major driver of most-pressing sustainability challenges such as climate change, unsustainable resource extraction, and altered biogeochemical cycles of N and P1-5. Food loss and waste is at the heart of the problem6,7. With 1/3 of food uneaten but lost/wasted, not only do resources consumed in producing the food ‘go down the drain’ but also the wasted food continues to brew health and pollution problems8,9. Here we show that food waste recovery and upcycling can effectively mitigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Applying this criterion is important in calculating this indicator, as a large proportion of kitchens did not disclose or quantify the number of food items procured. This indicator was calculated using Equation (5), where i represents the daily amount, and n is the total number of sample units in the case of surveys and the total number of quantification days in the case of live tracking.…”
Section: Calculating "Percentage Waste"mentioning
confidence: 99%
See 1 more Smart Citation
“…Applying this criterion is important in calculating this indicator, as a large proportion of kitchens did not disclose or quantify the number of food items procured. This indicator was calculated using Equation (5), where i represents the daily amount, and n is the total number of sample units in the case of surveys and the total number of quantification days in the case of live tracking.…”
Section: Calculating "Percentage Waste"mentioning
confidence: 99%
“…A new report by the World Wide Fund for Nature (WWF) has revealed that 2.5 billion tonnes or 40% of all food grown globally are lost or wasted [1]-approximately 1.2 billion tonnes more than previously estimated by FAO in 2011 [2][3][4]. This not only wastes huge amounts of natural and man-made resources employed in producing this food but also represents a lost opportunity for food security and the economy [5][6][7]. It is morally and ethically wrong to waste food fit for human consumption when 850 million people were still hungry and one out of three were malnourished in 2018 [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%